Foundry: Early learnings from the implementation of an integrated youth service network. Issue 4 (18th May 2021) - Mathias, Steve; Tee, Karen; Helfrich, Warren; Gerty, Krista; Chan, Godwin; Barbic, Skye Pamela
Abstract: AIMS: To provide the first profile of the demographic and service characteristics of young people (aged 12–24 years) who access Foundry, a provincial network of integrated youth health and social service centres in British Columbia, Canada and to share early learnings about implementation and service innovation. METHODS: Using a retrospective chart review, we conducted a census of all young people accessing a Foundry centre in a 'proof of concept' phase. Six centres were assessed between October 2015 and March 2018. Data included demographics, mental health service access history, service type the youth was seeking, and information about how they found out about the centre. RESULTS: A total of 4783 young people presented during this proof of concept period, for a total number of 35 791 visits. The most frequently accessed category of service was mental health/substance use (57%) followed by physical health (25%). Young people were most likely to be female, aged 15–19, and White. Youth demographic characteristics showed an over‐representation of Indigenous and LGBTQ2 youth and under‐representation of males and youth aged 20–24. Youth were most likely to learn about Foundry from a friend (44%) or family member (22%). Most youth (58%) reported that they would have gone 'nowhere' if not for Foundry. CONCLUSIONS: Foundry is a model of integrated health and social services delivery, focused on early intervention, prevention and accessibility, driven by the needs and priorities of young people and their families. Leveraging international integrated youth health service evidence, the model addresses urgent priorities in Canadian health service delivery.